Legal Analysis of Patent Registration through the Patent Cooperation Treaty in Indonesia: Benefit or Loss? - Caitlin Audrey Edelyne; Aurora Jillena Meliala (Lambung Mangkurat Law Journal, 2025)
This study aims to examine and analyze the legal protection of patents in Indonesia within the framework of the Patent Cooperation Treaty (PCT) system as an instrument to facilitate technology transfer, as well as to identify the key obstacles faced by inventors in utilizing it. The research employs a normative juridical method with statutory and conceptual approaches. The findings reveal that the regulatory framework governing the PCT system in relation to technology transfer has been accommodated in Article 20 of Law No. 13 of 2016 on Patents, which has since been amended by Government Regulation in Lieu of Law (Perppu) No. 2 of 2022. Nonetheless, the implementation of the PCT system faces several significant challenges, including regulatory disharmony due to the amendment of Article 20 that has led to liberal interpretations, the procedural complexity of PCT applications that demands substantial legal and technical knowledge, and the generally low level of literacy and understanding among Indonesian inventors regarding patent strategies linked to commercialization and technology transfer. Therefore, strategic measures are required to strike a balance between the protection of exclusive patent rights and the public interest in accessing and adapting technologies. Through an integrative approach oriented toward national capacity building, Indonesia has the potential to transition from a passive technology user to an active player in the global innovation ecosystem by optimizing the PCT system.